2018
DOI: 10.21608/jpp.2018.36633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Date and some Pre-Planting Treatments on Growth and Yield of Garlic

Abstract: and six pre-planting treatments on plant growth, yield and its components and chemical compounds of bulbs. The six pre planting treatments were T1: the control, T2: soaking garlic cloves (SGC) in water for 24 hour, T3: SGC in 5 ppm GA 3 for 24 hour, T4: SGC in water for 24 h and then placing in moist peat-moss for one day, T5: SGC in water for 24 h and then placing in moist peatmoss for two days and T6: SGC in water for 24 h and then placing in moist peat-moss until root initiation (after three days). The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
(6 reference statements)
3
2
0
Order By: Relevance
“…The lowest yield was record at the late planting date (1 November). Similar results were obtained by Hassan et al (2016) and El-Shabasi et al (2018).…”
Section: Storabilitysupporting
confidence: 91%
See 1 more Smart Citation
“…The lowest yield was record at the late planting date (1 November). Similar results were obtained by Hassan et al (2016) and El-Shabasi et al (2018).…”
Section: Storabilitysupporting
confidence: 91%
“…The lowest yield was scored at the late of planting date (1 November). Similar results were obtained by Hassan et al (2016) and El-Shabasi et al (2018). Besides, Ismail et al (2018) in south sinai obtained the interaction between planting dates on 15th Oct. or 1st Nov. and fertilizing plants with 100% of the recommended rate of N gave the highest values of each of dry weight of bulbs, leaves, and total dry weight/plant.…”
Section: Introductionsupporting
confidence: 80%
“…However, the lowest values of germination percentage after 30 days from planting was noticed by the control (T 7 ) whereas, T 5 exhibited the lowest values for all other traits. Similar results were reported by Rahman et al (2006), Ahmed and Hemada (2012) and El-Shabasi et al (2018) who reported that Sids-40 garlic clove seed soaking in water then placing in moist peatmoss until root initiation could be recommended to produce higher yield with better quality.…”
Section: Fig 2 Changes Values In All Studied Traits As Affected By Pre -Sowing Treatments On Garlic Plants (Average Of Both Seasons)supporting
confidence: 85%
“…In this respect, Wet peat moss layers are used by Abd El-Latif et al (2015) for accelerating germination of globe artichoke stumps in vernalization process. El-Shabasi, et al (2018) reported that soaking garlic cloves in water for 24h and then placing in moist peat moss until root initiation improved vegetative growth, increasing total produce and bulb quality. Clove sprouting and emergence are controlled mainly by temperature (Takagi, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Garlic cloves are typically obtained from plants that have been harvested in the late summer (e.g., in the Pacific Northwest region of the United States, from early July to mid-September) and then stored for planting in the autumn (mid-September to November) or, for some varieties, in the early spring (March) [5,6]. In order to prevent sprouting during storage and ensure quick germination and Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%